Shortfall of Strategic Governance and Strategic Management in the Czech Republic - Ochrana František (Central European Journal of Public Policy, 2016)
The article analyses the problems of strategic governance and strategic management of the Czechoslovak Government, as well as the Government of the Czech Republic in the years 1989-2016. It seeks the causes and factors that have caused the low levels of strategic governance and strategic management at the level of the ministries of the Czech Republic. It examines the problem from genetic and historical perspective, and from the organizational and human capacity to exercise strategic governance. The study is based on two pieces of empirical research within the ministries of the Czech Republic. It identifies the main cause of failure of strategic governance and strategic management at the level of the central government of the Czech Republic. These include, in particular, the persistent distrust of the ideas of strategic governance and strategic management held by the right-wing governments and the generally low capacity of governments of the Czech Republic to engage in strategic governance. The organizational structure of the central state administration lacks the strategic units that generate ideas for supporting strategic governance. The empirical research of the ministries of the Czech Republic also revealed that policy workers in Czech ministries dedicate a large proportion of their work time to operational and administrative activities at the expense of analytical and strategic activities. The changes require implementation of reforms within the public administration, which (among other things) will eliminate the existing causes and inhibiting factors regarding the lack of strategic governance in the Czech Republic.